Defining the impact of individual sample variability on routine immunoassay of serum free light chains (sFLC) in multiple myeloma. (3rd January 2013) - Murng, S. H. K.; Follows, L.; Whitfield, P.; Snowden, J. A.; Swallow, K.; Green, K.; Sargur, R.; Egner, W.
Summary Serum free light chain (sFLC) measurement has gained widespread acceptance and is incorporated into various diagnostic and response criteria. Non‐linearity and antigen excess are the main causes of 'variability' in the measurement of sFLC using immunoassay, but the impact of these on measurement has been unclear. We performed a retrospective evaluation using a dilutional strategy to detect these phenomena. A total of 464 samples in 2009 and 373 samples in 2010 were analysed for sFLC. Non‐linearity was detected in both high and apparently normal sFLC. Major non‐linearity of more than twofold is common in high kappa (20·2%) and lambda (14·1%). It is less common in samples with apparently normal levels – kappa (6·4%) and lambda (9·5%). 9·4% of kappa and 15·5% of lambda showed antigen excess at screening dilutions. 34·4% of the samples had either non‐linearity or antigen excess. We conclude that significant measurement variability is common in the measurement of sFLC. There is currently no reliable technique to detect non‐linearity phenomena unless a serial dilution strategy is applied to every analysis. We recommend that laboratories routinely reporting sFLC results for clinical services need appropriate strategies for addressing these issues. Clinicians should be aware of these limitations in interpretation of sFLC assay for individual patients. Future guidelines should adopt action thresholds which are grounded firmly in test performance parameters.